KONSEKUENSI PENERAPAN SISTEM NEGATIF DALAM PENDAFTARAN TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TERHADAP KEKUATAN SERTIFIKAT - CH. Anggia H.D.K.W. (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
The implementation of Land Registration based on PP No. 24/1997 has brought the significant benefit, especially for the holder of land rights to have the law assurance of their status as holder and also rights of their land. And the Other hand it also gives the law assurance for the third party (buyer and creditor) about the rights of the land which is intended to buy or to be made as collateral. The application of negative system in the land registration process brings a consequence. It is that the letter of rights issued by National Land Body (called land certificate), becomes strong evidence, meaning whenever there is no other evidence is able to prove otherwise concerning physically and legally data of the land the Judge will use the certificate as a proof of evidence.